Pengaruh Budaya Organisasi, Job Description dan Fasilitas Kerja Terhadap Kepuasan Kerja Pegawai Badan Pengelola Keuangan, Pendapatan dan Aset Daerah Kabupaten Tapanuli Selatan - Arhan Martas Siregar; Ira Kartika Pulungan; Ira Susyani Manullang; Horan Jawa; Arif Hasudungan Gultom; T. Ahmad Helmi; Sri Rahayu (Journal of Trends Economics and Accounting Research, 2023)
This formula research internal issue is how influence of organization culture on employees satisfaction. How influence of job description on employees satisfaction. How influence of job facility on employees satisfaction. How influence of organization culture, job description and job facility on employees satisfaction. This research target is to for know influence and analyze of organization culture on employees satisfaction. For know influence and analyze job description on employees satisfaction. For know influence and analyze job facility on employees satisfaction. For know influence and analyze organization culture, job description and job facility on employees satisfaction. Sample in this research amount to 82 employees. Technique analyze data which used in this research is analysis of regresi multiple linear. This research result explain of organization culture effect positive and significant on employees satisfaction. Job description effect positive and significant on employees satisfaction. Job facility effect positive and significant on employees satisfaction. Organization culture, job description and job facility effect and positive and significant on employees satisfaction.